Post-Partum Hemorrhage in Khost Post Graduate Medical Education Hospital - Sardar, Sakhi; Sharif, Sherzad Gul; Hemat, Mohammad Qadirshah; Sabari, Lailoma Anwar (Journal for Research in Applied Sciences and Biotechnology, 2022)
The leading cause of maternal deaths in both industrialised and developing nations is Post-Partum Haemorrhage (PPH). It results from deviations in one of four fundamental processes, with uterine atony constituting the majority of cases. It's crucial to have a diverse approach to management. It is considered the importance of oxytocin and prostaglandins, such as misoprostol, in therapy. Uterine tamponade and compression sutures, two recently created, less invasive therapeutic options, are quickly emerging as viable substitutes for the conventional procedures of pelvic devascularization and hysterectomy. Public health initiatives and medical measures meant to reduce maternal mortality from PPH, which differs significantly across developing and industrialised nations, are further examined. Dr. Sakhi Sardar and Dr. Sherzad Gul Sharif did this prospective observational research in the department of obstetrics and gynaecology at the Khost Provincial Hospital in Afghanistan. There were a total of 80 instances of Post-Partum Haemorrhage that met the criteria for inclusion. Data were gathered and examined in PPH patients who had both medicinal and surgical treatment. In the current research, more than 50% of patients needed blood and blood products, and 60% of cases were multigravida. The majority of Post-Partum Haemorrhage (PPH) cases in the current research were treated medically. uterine toxins (42.5 %) Early detection and prompt intervention made this feasible. In every situation, active management of the third stage of labour is advised. 70% of patients were handled medically, while the remaining 30% needed surgical intervention. Uterotonic medications and bimanual uterine compression were employed in medical care, although cervical and vaginal laceration repair was mostly needed in surgical management.